Antioxidant Profile of Different Types of Herbal Infusions and Teas Commercially Available in Mexico - Mabel, Treviño-Gómez Darytza; Javier, Sánchez-Alejo Ernesto; Cynthia, Gontes-Pérez Ixtaccihuatl; Jorge, Wong-Paz; Romeo, Rojas; Guadal, Martínez-Ávila Guillermo Cristian (American Scientific Research Journal for Engineering, Technology, and Sciences, 2017)
Different types of teas and herbal infusions were studied. Antioxidant properties and phenolics compounds were estimated. Camellia sinensis based teas presented the highest values for inhibition of free radicals such as DPPH· and ABTS·+. The results showed different values between teas (Camellia sinensis) and herbal infusions (as Hibiscus sabdariffa). Green tea presented the highest values for inhibition of lipid oxidation (95.03 ± 3.34 to 31.68 ± 14.50 %) and polyphenolics content (0.112 ± 0.018 to 1.343 ± 0.068 GAE mg mL-1). In HPLC test, suggested the presence of antioxidant compounds such as epsyringic acid, procyanidin among others phenolic compounds. This study concluded that mexican teas and herbal infusions have potential to provide several benefits for human health, due to phenolic compounds present in them.